Practical feng shui for your workplace making the most of your workplace for harmony, prosperity & success - Low, Albert (Pelanduk Publications, 1999)
Feng Shui is the ancient Chinese art of studying the unseen forces emitted by the elements of water, earth, wood, fire and metal. The force exert a profound influence on us and have a certain magnetic property which not only controls our physical well-being but also our mental attitudes. This book should be used as a guide in every office. It enlightens both owners and workers on the various aspects of Feng Shui in the workplace through realistic advice and clear illustrations. It covers not only the shape of buildings but also the various aspects of the office area: work environment, executive rooms, general sitting position, office equipment and so on.